The Development of Santai Esport Tournament Management System - ZALIFF,; Nurezayana Zainal, (Applied Information Technology And Computer Science, 2024)
The "Santai Esports Tournament Management System" project deals with common problem in the esports industry. Santai Esports' current manual and paper-based methods have led to inefficiencies and errors in tournament organization, impacting competitions negatively. Engaging the gaming community on social media has been challenging, and cash distribution for winnings poses security risks. This project aims to modernize tournament management and financial transactions, replacing manual processes with automated systems for transparency and efficiency. Employing the Prototyping Model allows iterative development, ensuring user-focused design improvements. The system, tailored for organizers and participants, streamlines tournament management, financial transactions, and serves as a centralized hub. The anticipated outcome is a user-friendly platform simplifying tournament organization, improving financial procedures, enhancing community engagement, and ensuring a secure gaming environment. This system supports the growth of the esports community within Santai Esports.